Professional selfdetermination as the condition of the professional becoming of the personality of the students of the PTE - MOSKIN, Sergey (Continuing Professional Education: Theory and Practice, 2019)
The problem of professional selfdetermination of the personality of the students in the PTE is examined in the article – as the condition of their professional becoming; research actuality is grounded in the theoretical and experimental context; criteria are certain, indexes and psychodiagnostical tool of study of the professional selfdetermination personality of the students; materials of empiric research are analyzed; the degree of formed of professional is exposed to the selfdetermination of the personality of the students on the stage of entry to the PTE.